Surgical Approach for Recurrent Plunging Ranula in a Young Girl – A Case Report - Gazali, Muhammad; Fauzi, Abul; Amelia, R. (Hasanuddin University, 2021)
Introduction: Two variants have been described in the literature: a simple oral ranula and the deep diving or plunging ranula. Plunging ranulas arise when a simple ranula extends beyond the floor of the mouth into the neck. A plunging or diving ranula is a rare mucous fluid collection in the submandibular or parapharyngeal space resulting from damage or rupture of one or more ducts of the sublingual gland. An accurate diagnosis and an appropriate treatment plan are fundamental for a successful treatment of ranulas. Regardless of the surgical technique, conservative maneuvers associated with careful clinical monitoring were indispensable for the longevity and success of treatment. Objective: Excision of sublingual and submandibular gland be an option for this case with extraoral approach. Case: A 10-year-old girl presented with a chief complaint of a large swelling of the right submandibular, which had recurred after marsupialization. The clinical diagnosis was plunging ranula. Histopathological examination revealed heterotropia salivary gland with reactive follicular hyperplasia. Result: Histopathology examination reported as heterotopia salivary gland and reactive follicular hyperplasia can be parallel with pathophysiology of this case. The obstruction of salivary gland this patient association with anatomy anomalies or ectopic of the salivary gland. Evaluation post surgery shows no dysfunction of lingual and facial nerve. The treatment was successful with no recurrence was reported.Conclusion: This paper highlights a case report of recurrent plunging ranula was treated with extraoral approach be the method of choice for the success of treatment.